Antioxidant Activity of Mud Crabs (Scylla Serrata) in the Kawaliwu Waters of Sinar Hading Village, Lewolema District - Sogen, Santoris Gowing; Nawastuti, Dati; Batafor, Yosephina M. J. (Civiliza Publishing, Indonesia., 2025)
Kawaliwu waters are one of the areas with high potential for mangrove crabs. This study aimed to examine the antioxidant potential of mangrove crabs (Scylla serrata) collected from Kawaliwu waters in Sinar Hading Village, Lewolema District. This research method was experimental and employed a quantitative descriptive approach. Mangrove crab samples were prepared, dried, and extracted using 70% ethanol using the maceration method. The antioxidant activity of the extracts was tested using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The results showed that antioxidant activity increased with increasing extract concentration. The IC₅₀ (Inhibition Concentration 50%) value of the mangrove crab extract was 65.25 ppm, which is categorized as a strong antioxidant. This finding indicates that mangrove crabs possess bioactive compounds with potential as a source of natural antioxidants.